A Performance Evaluation for Software Defined Networks with P4 - Omesh A. Fernando; Hannan Xiao; Joseph Spring; Xianhui Che (Network, 2025)
The exponential growth in the number of devices connected via the internet has led to the need to achieve granular programmability for increased performance, resilience, reduced latency, and jitter. Software Defined Networking (SDN) and Programming Protocol independent Packet Processing (P4) are designed to introduce programmability into the control and data plane of networks, respectively. Despite their individual potential and capabilities, the performance of combining SDN and P4 remains underexplored. This study presents a comprehensive evaluation of SDN with data plane programmability using P4 (SDN+P4) against traditional SDN with Open vSwitch (SDN+OvS), aimed at answering the hypothesis that combining SDN and P4 strengthens the control and data plane programmability and offers improved management and adaptability, which would provide a platform with faster packet processing with reduced jitter, loss, and processing overhead. Mininet was employed to emulate three distinct topologies: multi-path, grid, and transit-stub. Various traffic types were transmitted to assess performance metrics across the three topologies. Our results demonstrate that SDN+P4 outperform SDN+OvS significantly due to parallel processing, flexible parsing, and reduced overhead. The evaluation demonstrates the potential of SDN+P4 to provide a more resilient and stringent service with improved network performance for the future internet and its heterogeneity of applications.